Introducing a sensor to measure budburst and its environmental drivers - Kleinknecht, George J.; Lintz, Heather E.; Kruger, Anton; Niemeier, James J.; Salino-Hugg, Michael J.; Thomas, Christoph K.; Still, Christopher J.; Kim, Youngil (Frontiers in Plant Science, 2015)
Budburst is a key adaptive trait that can help us understand how plants respond to a changing climate from the molecular to landscape scale. Despite this, acquisition of budburst data is currently constrained by a lack of information at the plant scale on the environmental stimuli associated with the release of bud dormancy. Additionally, to date, little effort has been devoted to phenotyping plants in nature due to the challenge of accounting for the effect of environmental variation. Nonetheless, natural selection operates on natural populations, and investigation of adaptive phenotypes in situ is warranted and can validate results from controlled laboratory experiments. In order to identify genomic effects on individual plant phenotypes in nature, environmental drivers must be concurrently measured and characterized. Here, we designed and evaluated a sensor to meet these requirements for temperate woody plants. It was designed for use on a tree branch to measure the timing of budburst together with its key environmental drivers, temperature and photoperiod. Specifically, we evaluated the sensor through independent corroboration with time-lapse photography and a suite of environmental sampling instruments. We also tested whether the presence of the device itself on a branch influenced the timing of budburst. Our results indicated the following: the budburst sensor’s digital thermometer closely approximated a thermocouple touching plant tissue; the photoperiod detector measured ambient light with the same accuracy as time lapse photography; the phenology sensor accurately detected the timing of budburst; and the sensor itself did not influence bud phenology of Populus clones. Among other potential applications, future use of the sensor can provide plant phenotyping at the landscape level for integration with landscape genomics.